2013
DOI: 10.2478/amm-2013-0021
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Oxidation Behaviour of Tial8Nb Alloy

Abstract: The goal of this work is to determine the effect of niobium on the kinetics and mechanism of Ti-Al oxidation in air. In order to compare the oxidation kinetics of Ti-Al and Ti-Al with the addition of niobium, isothermal oxidation was performed on Ti-48Al and Ti-46Al-8Nb (in at.%) alloys at 1073 K in synthetic air. Cyclic oxidation of Ti-46Al and Ti-46Al-8Nb alloys was carried out in laboratory air for 42 cycles (1 cycle, 24 hrs). The morphology, as well as chemical and phase composition of the oxidation produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 1 publication
0
5
2
Order By: Relevance
“…Decomposition of TiN, additionally accelerates degradation of the exposed material, due to the further development of non-protective TiO 2 phase and due to release of free N 2 . In contrast to present study, Przybylski et al 19 found that TiN formed in Ti46Al8Nb alloy under isothermal oxidation at 800°C in synthetic air.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Decomposition of TiN, additionally accelerates degradation of the exposed material, due to the further development of non-protective TiO 2 phase and due to release of free N 2 . In contrast to present study, Przybylski et al 19 found that TiN formed in Ti46Al8Nb alloy under isothermal oxidation at 800°C in synthetic air.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to present study, Przybylski et al 19 found that TiN formed in Ti46Al8Nb alloy under isothermal oxidation at 800uC in synthetic air.…”
Section: Tialcr Systemcontrasting
confidence: 99%
See 2 more Smart Citations
“…These factors all affect the oxidation resistance, however, no systematic studies have been carried out in terms of oxidation kinetics, spalling form and delamination characteristics of oxide film. Studies into the oxidation of TiAl alloys are helpful in understanding the oxidation resistance of the alloy, and, at the same time, suitable means of oxidation resistance can be found according to the oxidation degree of the alloy during the oxidation process [10][11][12] . Therefore, further research regarding the oxidation behavior of the TiAl alloy becomes more urgent.…”
mentioning
confidence: 99%